1968
DOI: 10.4141/cjss68-008
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OF THE INORGANIC AND ORGANIC pH-DEPENDENT CATION EXCHANGE CAPACITY OF THE B HORIZONS OF PODZOLIC AND BRUNISOLIC SOILS

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1970
1970
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Broadbent & Bradford (1952) showed that most organic CEC sites were probably carboxyl groups or phenolic or enolic hydoxyl groups, and these will dissociate to very different extents in soils of different pH values. Hallsworth & Wilkinson (1958) (see Table 2) and Clark & Nichol (1968) showed organic CEC varied with soil pH. Consequently the soil was saturated (with Ba or Ca) in both methods at pH 8'1 (that used in Bascomb's method to avoid dissolving Ca from chalk), so that they were directly comparable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Broadbent & Bradford (1952) showed that most organic CEC sites were probably carboxyl groups or phenolic or enolic hydoxyl groups, and these will dissociate to very different extents in soils of different pH values. Hallsworth & Wilkinson (1958) (see Table 2) and Clark & Nichol (1968) showed organic CEC varied with soil pH. Consequently the soil was saturated (with Ba or Ca) in both methods at pH 8'1 (that used in Bascomb's method to avoid dissolving Ca from chalk), so that they were directly comparable.…”
mentioning
confidence: 99%
“…Williams (1932) and Hallsworth & Wilkinson (1958) used multiple regression analysis to relate cation exchange capacity (CEC) in several soils to percentage organic matter (OM) and percentage clay, and thence to calculate the average values of the CECs of OM and clay. For individual soils, Davies & Davies (1965) and Clark & Nichol (1968) measured the CEC before and after oxidizing the OM with hydrogen peroxide. Evans (1959) measured the CEC of extracted humic acid from an old grassland soil, but this type of measurement does not give the total ' organic' CEC or enable the 'mineral' CEC to be derived.…”
mentioning
confidence: 99%